Influence of coaches on sources of enjoyment in youth basketball - Carvalho, Humberto M. (2017)
We examined the influence of coaches on sources of enjoyment of youth basketball players accounting for differences in chronological age, biological maturity status and years of training experience. Fifty-eight male basketball players aged 9.5 to 15.5 years were considered from a youth club. Three coaches supervising yearly age group teams from under 11 to under 15 teams were considered. Variables included chronological age, estimated age at peak height velocity, years of training experience, stature, body mass and sitting height by anthropometry; Sources of Enjoyment in Youth Sport Questionnaire was used. Multilevel modelling was used to partition variance between groups and control the influence of age and maturity status on enjoyment. Variance partition coefficients derived from multilevel null models showed a substantial variation by coach for age, maturity status and body dimensions. For the sources of enjoyment dimensions it was apparent an influence of the coach mostly for positive parental involvement. Controlling separately for age and somatic maturity status category, substantial variation by coach became apparent for self-referenced competencies and affiliation with peers, and the influence of coach was removed for positive parental involvement. After controlling variation associated to the coach the influence of age and maturity status remained present. The influence of the coach in the sources of enjoyment in adolescent basketball was apparent in adolescent basketball players. Furthermore, coaches´ influence became more apparent after accounting for age and biological maturity status differences between players.